Optic Disc and Macula Localization from Retinal Optical Coherence Tomography and Fundus Image - Rodiah Rodiah; Sarifuddin Madenda; Diana Tri Susetianigtias; Dewi Agushinta Rahayu; Ety Sutanty (International Journal of Electrical and Computer Engineering (IJECE), 2018)
This research used images from Optical Coherence Tomography (OCT) examination as well as fundus images to localize the optical disc and macular layer of retina. The researchers utilized the OCT and fundus image to interpret the distance between macular center and optic disc in the image. The distance will express the area of macula that can be employed for further research. This distance could recognize the thickness of macula parameters diameter that will be used in localizing process of optic disc and macula. The parameters are the circle radius, the size of window’s filter, the constant value and the size of optic disc element structure as well as the size of macula. The results of this study are expected to improve the accuracy of macula detection that experience the edema.